Cardiotocography in practice: a qualitative study to explore obstetrical care professionals’ experiences with using cardiotocography information in Dutch practice - P W Teunissen; A Romijn; P C A M Bakker (BMJ Open, 2023)
Objective This study aimed to explore obstetric care professionals’ experiences with using cardiotocograph (CTG) information and how they employ this tool in their practice.Design Qualitative study, involving 30 semi-structured interviews and two focus group sessions. Conventional content analysis was used for data analysis.Setting Amsterdam University Medical Centers in the Netherlands.Participants In total, 43 care professionals participated. The respondents included obstetricians, residents in obstetrics and gynaecology, junior physicians, clinical midwives and nurses.Findings Three main categories were identified that influenced the use of cardiotocography in practice; (1) individual characteristics involving knowledge, experience and personal beliefs; (2) teams involving collaboration in and between shifts and (3) work environment involving equipment, culture and continuing development.Conclusion This study underlines the importance of teamwork when working with cardiotocography in practice. There is a particular need to create shared responsibility among team members for cardiotocography interpretation and appropriate management, which should be addressed in educational programmes and regular multidisciplinary meetings, to allow learning from colleagues’ perspectives.